Knowledge and Attitude of Mothers Regarding Oral Rehydration Salt - Abida Sultana, Rizwana Riaz, Riaz Ahmed, Riffat Khurshid (Journal of Rawalpindi Medical College, 2010)
Background: To assess the knowledge, attitude and behaviour of mothers about Oral Rehydration Salt (ORS). Methods: In this cross-sectional descriptive study a total of 320 mothers were enrolled by convenience sampling. Data was collected by means of semi-structured questionnaire. Questionnaire asked information regarding the knowledge of mothers about ORS, its availability in the market, method of preparation, source of information about ORS and the role of ORS in the management of diarrhoea. Results: Of the total 320 mothers, 80% respondents were literate. 61.87% mothers belonged to middle social class and among those 44% seemed to have adequate knowledge pertaining to ORS preparation and its significance in the management of diarrhoea. Only 4.06% mothers did not know about ORS. Information regarding availability of ORS was found to be accurate among 86.87% mothers. Most of the mothers (37.19%) got information about ORS from doctors followed by media (25%) and their mothers (20%). Conclusion: Knowledge about ORS was found to be adequate among educated mothers belonging to middle socioeconomic status. Information pertaining to ORS was mainly imparted by the health care providers.